Diálogos entre saberes e o ensino de Ciências com base nas vivências dos barqueiros no entorno do Rio Acará - ALVES, Eliene da Silva (2022)
This paper, as the result of research, aims to further the visibility of local knowledge combined with the teaching of science. The objective was to observe the production and ways of propagating the water expertise, especially the ones from the boatmen in the region of the Acará river. In the study, centered in the qualitative approach, we have used ethnography resources seem from a perspective of deepening the learning of it. Therefore, raising field work and the construction of knowledge. Moreover, in the theoretical references there are authors such as Castro (1998), Brandão (1981; 2008), Araújo et al. (2011), Neto; Furtado (2015), Alves; Pojo (2020), among others. We noted the constant movements from one edge of the river to another, in which the boatmen share trades and knowledges in their trajectories of life and work. The results indicate a close relationship to the waters, dictated by the subjects’ feelings and values and the existing interaction among the teaching of science through the thematic field of the waters.